Effect of Curcumma, Zn-Proteinate, and Cu-Proteinate Supplements on Milk Production of Subclinical Mastitis Fries Holland Cows - Taspirin, DS; Makin, M; Manalu, W; Tanuwiria, UH (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
The objective of the research was to find out the effect of Curcumma, Zn-proteinate, and Cu-proteinate supplementation on subclinical mastitis status in term of 4% FCM milk production. The research was conducted using 24 heads of lactating dairy cows in Randomized Block Design with six treatments, and four groups of milk production as replication i.e. I= >14 kg/day ; II= 12-13.99 kg/day ; III= 10-11.99 kg/day; IV= <10 kg/day. Treatments were: R1 (Control); R2 (R1 + 2% Zn proteinate); R3(R1 + 2% Cu-proteinate); R4(R1 + 2% Curcumma); R5(R1 + 2% Zn-proteinate + 2% Cu-proteinate); R6 (R1 + 2% Zn-proteinate + 2% Cu-proteinate + 2% Curcumma). Parameters observed were 4%FCM milk production and subclinis status. The results showed that ration supplemented with Curcumma, Zn-proteinate, and Cu-proteinate decreased mastitis subclinic status and 4% FCM milk production increased significantly. Supplementation of Curcumma, Zn-proteinate, and Cu-proteinate resulted is the best for decrease in subclinical mastitis indicator and increase 4% FCM milk production. (Animal Production 12(1): 16-20 (2010)Key Words : dairy cows, subclinic mastitis, curcumma, Zn-proteinate, and Cu-proteinate